Improving Office Procedure System at Marketing Department of DLQ Electrical Engineers in Cubao Branch: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The DLQ Electrical Engineers is a private institution that promotes collaboration among electrical practitioners and advances technology through carefully designed educational and training programs. It is the only accredited professional organization for electrical practitioners by the Professional Regulation Commission. This study aims to improve the office procedure system at the Marketing Department of DLQ Electrical Engineers in the Cubao Branch. To learn about the organization and find potential problems that might eventually affect procedures, the researchers used a qualitative approach and a descriptive study design. The participants in the study were mostly female employees of the Marketing Department. The researchers used a descriptive survey questionnaire to gather information on proposed solutions and additional procedures. After analyzing the data, it was found that most respondents agreed with the proposed solutions and additional procedures, which have a high potential to enhance the overall operations of the department. Therefore, the proposed recommendations and procedures are deemed feasible in improving the office procedure of the Marketing Department of the organization.
Keywords: Office Procedure; Organization; Process; Marketing